Crack detection for spur gears with asymmetric teeth based on the dynamic transmission error. (March 2019) - Doğan, Oğuz; Karpat, Fatih
Highlights: A finite element model is used to calculate single tooth stiffness. TVMS of spur gears with asymmetric tooth profile calculated for different crack levels. 4-DOF dynamic model is developed to calculate dynamic transmission error. Effects of crack levels on TVMS and DTE are investigated numerically. Early stage tooth errors can be detected by the variation of DTE. Abstract: Gears are one of the most important power transmission elements in every area of the industry. Because of its importance, the gear design must be carefully performed. Unfortunately, due to the changing of the boundary conditions, gears are exposed to failures such as cracks, pitting, tooth missing etc. during the operation. Thus the gear diagnostic and monitoring become a very critical phenomenon for the gearboxes. A dynamic transmission error (DTE) based numerical fault detection model is proposed. Firstly, numerical finite element model is created to calculate single tooth stiffness with different crack levels. Furthermore, the model is used for the asymmetric gear profile which has a great importance nowadays for different areas. After that, the time-varying mesh stiffness is calculated by using single tooth stiffness with different crack levels for both symmetric and asymmetric types of the gears. To understand the effects of the gear cracks along the tooth thickness on dynamic transmission error of the gear system and to detect the gear crack faults for symmetric and asymmetric gear profiles, a four-degree of freedom dynamic model is created. The results show that with the increment of the crack level, the mesh stiffness of the gears is decreased.